Change Profiles and Functional Targets of MicroRNAs in Type 2 Diabetes Mellitus Patients with Obesity - Lu, Guanhua; Gao, Huanhuan; Dong, Zhiyong; Jiang, Shuwen; Hu, Ruixiang; Wang, Cunchuan (Diabetes & metabolism journal, 2023)
Background: MicroRNAs (miRNAs) exert an essential contribution to obesity and type 2 diabetes mellitus (T2DM). This study aimed to investigate the differences of miRNAs in the presence and absence of T2DM in patients with obesity, as well as before and after bariatric surgery in T2DM patients with obesity. Characterization of the common changes in both was further analyzed.Methods: We enrolled 15 patients with obesity but without T2DM and 15 patients with both obesity and T2DM. Their preoperative clinical data and serum samples were collected, as well as 1 month after bariatric surgery. The serum samples were analyzed by miRNA sequencing, and the miRNAs profiles and target genes characteristics were compared.Results: Patients with T2DM had 16 up-regulated and 32 down-regulated miRNAs compared to patients without T2DM. Improvement in metabolic metrics after bariatric surgery of T2DM patients with obesity was correlated with changes in miRNAs, as evidenced by the upregulation of 20 miRNAs and the downregulation of 30 miRNAs. Analysis of the two miRNAs profiles identified seven intersecting miRNAs that showed opposite changes. The target genes of these seven miRNAs were substantially enriched in terms or pathways associated with T2DM.Conclusion: We determined the expression profiles of miRNAs in the obese population, with and without diabetes, before and after bariatric surgery. The miRNAs that intersected in the two comparisons were discovered. Both the miRNAs discovered and their target genes were closely associated with T2DM, demonstrating that they might be potential targets for the regulation of T2DM.